FINANCIAL FEASIBILITY OF PURSE SEINE FISHERIES IN BALIMU VILLAGE, SOUTH LASALIMU OF BUTON REGENCY - Abdul Sarifin; Azwar Sidiq; Wa Ode Harliyanti Unga; Aminur Aminur (Jurusan Perikanan dan Kelautan, 2021)
Purse siene fishery is a capital-intensive and labor-intensive business, but it carries considerable business risk due to climate change, increased operating costs, decreased fish stocks and unstable fish prices. The purpose of this study was to determine the financial feasibility of a purse seine fishery business in Buton Waters. This research was conducted in October 2020 in Balimu Village, South Lasalimu District, Buton Regency, Southeast Sulawesi Province. This study used a survey method using a questionnaire. Data were analyzed descriptively quantitative. The results showed that the average amount of profit earned during the peak fishing season was IDR 277,263,939 / month. The NPV value is IDR 4,021,035,338 (> 0), the Net B / C Ratio value is 6.63 (> 1), the R/C Ratio value is 6.10 (> 1), the IRR value is 2.87 ( > 15% interest rate), the payback period is 8 months and 5 days, and the ROI value is 2.31%. Thus, purse seine fishery activities in Balimu Village, South Lasalimu Subdistrict during the peak fishing season are financially feasible.